Evaluation of antibacterial activities from major bioactive constituents of the whole plant of Hedyotis corymbosa - Desy Ambar Sari; - Harijono; Chi-I Chang (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
Hedyotis corymbosa is locally known as rumput mutiara from the Rubiaceae family, widely distributed in tropical regions of Asia. Researchers provided scientific evidences the beneficial impact of this plant for pharmacologic alactivity. This study aimed to isolate and evaluate the bioactive constituents based on their biological activities. In this study, the whole plant of H. corymbosa was extracted using methanol. Extract of H. corymbosa was sequentially partitioned using ethyl acetate and n-butanol. The ethyl acetate layer was further fractionated and isolated using chromatographic techniques to obtain the pure compounds. The bioactive compounds structure was determined using spectroscopic analysis especially the Nuclear Magnetic Resonance (NMR). The investigation of H. corymbosa resulted in the isolation of eight compounds, were identified as ursolic acid, 3β-hydroxyolean-11-en-28,13β-olide, β-sitosterol, stigmastane-3,6-dione, ferulic acid, scopoletin, 2-hydroxy-1-methoxyanthraquinone, 3-hydroxy-1,2-dimethoxyanthra-quinone. The antimicrobial effect of the crude extract, partitions and fractions were evaluated using agar well diffusion for antimicrobial susceptibility test and for the pure compounds were evaluated using minimum inhibitory concentration. The ethyl acetate layer and crude extract displayed the higher antimicrobial activities than n-butanol and water layer. The Minimum Inhibitory Concentration (MIC) for the pure compound was shown that most of the compounds have the ability to inhibit human pathogenic bacteria with average 100 µg/mL. The antimicrobial activities showed by the crude extracts, fractions, and pure compounds of H. corymbosa can be used as a commercial product for antimicrobial agent against S. aureus, S. enterica, E. coli and B. substilis.